2005
DOI: 10.1080/00224490509552274
|View full text |Cite
|
Sign up to set email alerts
|

Condom use, frequency of sex, and number of partners: Multidimensional characterization of adolescent sexual risk‐taking

Abstract: Sexual health research often relies on single risk indicators. However multi-variable composites may better capture the underlying construct of risk-taking. Latent Profile Analysis identified subgroups based on condom use consistency, partner numbers, and sex frequency among 605 adolescents. Three profiles were identified for each of grades 8 to 10 (Condom Users, Few Partners, and Risk-Takers) and 4 in grades 11 and 12 (Condom Users, One Partner Two Partners, and Risk-Takers). Inconsistent condom use groups re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 26 publications
5
73
1
4
Order By: Relevance
“…This may be a unique and noteworthy descriptor of this particular population, in comparison to other samples such as school-based samples of African American adolescent girls and boys, where both Beadnell et al 5 and Newman and Zimmerman 11 found evidence of a subgroup who used condoms consistently with a moderate number of sexual partners. The current findings suggest that assessing and addressing barriers to consistent condom use is important when providing healthcare services to African American female adolescents.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This may be a unique and noteworthy descriptor of this particular population, in comparison to other samples such as school-based samples of African American adolescent girls and boys, where both Beadnell et al 5 and Newman and Zimmerman 11 found evidence of a subgroup who used condoms consistently with a moderate number of sexual partners. The current findings suggest that assessing and addressing barriers to consistent condom use is important when providing healthcare services to African American female adolescents.…”
Section: Discussionmentioning
confidence: 67%
“…Although multiple evidence-based HIV-prevention interventions have been developed and rigorously evaluated for adolescent populations, 3 limited resources (cost, personnel, space, time) support the utility of identifying youth at highest risk for infection. Numerous research efforts over the past several decades have uncovered a range of individual risk factors contributing to HIV infection among African American girls, including infrequent condom use, 4 multiple sexual partners, 5 substance use, 6 low self-esteem, 7 interpersonal trauma (e.g., child sexual abuse), 8 and ineffective coping styles. 9 However, epidemiologic data have highlighted that these behaviors do not occur in isolation and that HIV risk is heightened by the co-occurrence of such risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diversos estudos, realizados no âmbito dos comportamentos sexuais, consideram os jovens um grupo prioritário de intervenção (Almeida et al, 1996;Nodin, 2001) devido ao início da actividade sexual ser cada vez mais cedo (Lindsay, Smith & Rosenthal, 1997;Nodin, 2001), à duração dos relacionamentos, à existência de parceiros ocasionais e ao uso inconsistente dos métodos contraceptivos e do preservativo (Beadnell et al, 2005;Brook et al, 2006).…”
unclassified